Hepatic Portal Venous Gas: A Report of Two Cases and a Review of the Epidemiology, Pathogenesis, Diagnosis and Approach to Management - Saleh Alqahtani; Carla S Coffin; Kelly Burak; Fred Chen; John MacGregor; Paul Beck (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatic portal venous gas (HPVG) is a rare condition that occurs when intraluminal gas and/or gas produced by intestinal bacteria enters the portal venous circulation. The most common precipitating factors include ischemia, intra-abdominal abscesses and inflammatory bowel disease. However, HPVG has recently been recognized as a rare complication of endoscopic and radiological procedures. Earlier studies advised immediate surgical intervention, but according to current recommendations, in some settings, HPVG can be managed conservatively. The present study reports two cases of HPVG; one that occurred following colonoscopy in a patient with severe Crohn’s disease and one in a patient with graft-versus-host disease.